The Evolution of Beauty: How Darwin’s Forgotten Theory of Mate Choice Shapes the Animal World – and Us - Gregory, Geoff (New Zealand Science Review, 2017)
​Professor Richard Prum is an obsessive ornithologist, who, in forty years of field observations, is over one-third of the way towards achieving his boyhood ambition of watching every one of the ten thousand or more bird species in the world and researching their behaviour. He knows his subject intimately.This book parades the facts that have led him to revisit Darwin’s second great theory – the independent evolutionary mechanism of sexual selection. He calls this ‘Darwin’s really dangerous idea’ – dangerous because it shows that Darwin’s first great theory – natural selection – which is nowadays widely assumed to have all-embracing power, cannot fully explain some aspects of the evolution of species.